United Republic of Tanzania : Fifth Review Under the Policy Support Instrument, First Review Under the Standby Credit Facility, and Requests for a Waiver of Nonobservance of a Performance and Assessment Criterion, Rephasing of the Standby Credit Facility Arrangement and Modification of Performance and Assessment Criteria-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Tanzania. (IMF Staff Country Reports; Country Report ;, 2013)
Tanzania's macroeconomic outlook is favorable with buoyant growth and declining inflation. The Executive Board of the International Monetary Fund (IMF) commended its prudent policy management and progress in stabilizing the economy. The country's 2012-13 budget appropriately balances the development and social spending needs with the debt-stabilizing objective. The country's structural reforms aim to secure fiscal sustainability and support a strong economic expansion in the medium term. The Directors concluded that the floating exchange regime would continue to provide helpful flexibility to preserve its macroeconomic stability.